Walking on Eggshells: A Study of Egg Use in Anglo‐Scandinavian York Based on Eggshell Identification Using ZooMS. (18th December 2013) - Stewart, John R. M.; Allen, Richard B.; Jones, Andrew K. G.; Kendall, T.; Penkman, K. E. H.; Demarchi, B.; O'Connor, T.; Collins, M. J.; Bejenaru, L.; Serjeantson, D.
ABSTRACT Eggshell is a potentially common archaeological resource, but it tends to be ignored. The recent development of ZooMS (zooarchaeology by mass spectrometry) as a rapid and robust system for taxonomic identification of preserved eggshell fragments has facilitated new insights into patterns of egg use in the past. This paper presents a case study of egg use at two sites in Anglo‐Scandinavian York (Hungate and Coppergate). The results described below suggest that the relative prevalence of goose eggshell may become a useful indicator of status, consistent with other characteristics of the two sites, and also demonstrate an apparent lack of exploitation of eggs of wild birds in York during the Anglo‐Scandinavian period. These results highlight the interpretative potential of eggshell, which can now begin to be more fully explored. Copyright © 2013 John Wiley & Sons, Ltd.